New Paradigm Of Abuse Of Power On Discretion After Government Administration Act - Hidayat Pratama Putra (Faculty of Law, University of Mataram, 2018)
Discretion is one of government actions that are very vulnerable to abuse of power in it. Law Number 30 Year 2014 on Government Administration as a legal provision in the field of state administration currently regulates in detail related to discretion, abuse of power, and abuse of power in discretion in particular. This paper discusses the regulation related to abuse of power that has a paradigm shift based on Law Number 30 Year 2014 on Government Administration and benchmark it in discretion. The Government Administration Act builds a new paradigm of abuse of power by interpreting broadly abuse of power comprising beyond authority, misuse of authority and arbitrary. There are several indicators to show that discretion can be considered as abuse of power, namely: • Contrary to the Act and/or the principle of good governance; Notwithstanding the purpose of discretion or the purpose of the state in general; Breaking discretionary procedures; Beyond the Authority (onbevoegdheid); And/or has no basis of authority.